Changes in the nutritional, flavor, and phytochemical properties of Citrus reticulata Blanco cv. ‘Dahongpao’ whole fruits during enzymatic hydrolysis and fermentation - Li, Yurong; Guo, Long; Mao, Xiaoxue; Ji, Chen; Li, Wenji; Zhou, Zhiqin (Frontiers in Sustainable Food Systems, 2024)
Introduction Currently, the large-scale consumption of fresh citrus fruits in the form of juices, jams, and purees results in significant quantities of waste consisting of citrus peels, pulp, and seeds. Methods To improve the utilization rate of whole citrus fruits and reduce the generation of processing waste, the best pre-optimized enzymatic fermentation conditions were used to treat whole citrus fruits and to analyse the changes in nutritional and active components (Enzymatic: pectinase, cellulase, hemicellulase added at a ratio of 1:1:1 for 63.326 min at a temperature of 60°C, with 0.506% of each enzyme added; Fermentation: Lacticaseibacillus rhamnosus TR08, Lactiplantibacillus plantarum subsp. Plantarum CICC 6257, and Limosilactobacillus fermentum CCFM1139 were added at a ratio of 1:1:1 for 30 h, with the concentration was 108 CFU/mL, and the total amount added was 6%). Results Results showed that after enzymatic hydrolysis, the mineral elements (Nitrogen, phosphorus), total amino acid, vitamin C, and organic acid content increased. For soluble sugars, the contents of fructose and glucose increased, whereas the sucrose content decreased. Fermentation had a minimal effect on the mineral content; however, the total amino acid, vitamin C, and soluble sugar contents decreased. Additionally, when comparing the samples after enzymatic fermentation to those after enzymatic hydrolysis alone, the total phenols, total flavonoids, carotenoids and antioxidant activities were significantly increased by 1.39, 1.49, 1.21 and 3.79 folds, respectively. Discussion This study addresses the challenges of utilizing fruit residue in the current market, including high treatment costs and environmental pollution, by providing a novel perspective on the enzymatic hydrolysis and fermentation of whole red oranges. Furthermore, it aims to improve the nutritional, functional, and health benefits of citrus fruit products.